The evolution of Darwinism : selection, adaptation, and progress in evolutionary biology - Shanahan, Timothy, 1960- (Cambridge University Press, 2004)
No other scientific theory has had as tremendous an impact on our understanding of the world as Darwin's theory as outlined in his Origin of Species, yet from the very beginning the theory has been subject to controversy. The Evolution of Darwinism focuses on three issues of debate - the nature of selection, the nature and scope of adaptation, and the question of evolutionary progress. It traces the varying interpretations to which these issues were subjected from the beginning and the fierce contemporary debates that still rage on and explores their implications for the greatest questions of all: Where we come from, who we are and where we might be heading. Written in a clear and non-technical style, this book will be of use as a textbook for students in the philosophy of science who need to become familiar with the background to the debates about evolution.